MENINGKATKAN KEBIASAAN BERTANYA SISWA DALAM PROSES PEMBELAJARAN MELALUI OPTIMALISASI LAYANAN BIMBINGAN KELOMPOK PADA SIWA SMP NEGERI 1 ANGSANA TANAH BUMBU - Ngadikem Ngadikem (JURNAL SOCIUS, 2013)
This study aims to describe kaktivan, motivations, habits grader asked VIIIA, B and C, SMP Negeri 1 Angsana Land of Spices on the subject of the habit of asking students can be enhanced through learning strategy group counseling services model. The research method used in the study of this class action is a method of qualitative analysis, which essentially emphasizes the depiction of business matters relating to the increased activity of motivation in depth. With this qualitative analysis highlights the main issues in particular deepening activity of motivation in the learning process in schools. The research process began in June 2012 to August 2012, the number of samples of 23 people from the class VIIIA, B and C SMP Negeri 1 Angsana Land of Spices.The results showed that: (1) activity of, motivation to improve learning habits graders asked VIIIA, B and C, SMP Negeri 1 Angsana Land of Spices during use learning strategies to increase group counseling services (2) activity of, motivation habit of asking students grade VIIIA, B and C, SMP Negeri 1 Angsana Land of Spices for using learning strategies group counseling services can be improved. (3) Response grader VIIIA, B and C SMP Negeri 1 Angsana Land of Spices on the use of learning strategies counseling services group showed that students enjoy learning in the learning process by learning strategy group counseling services.Key words: Students motivation, learning strategy, and social studies